PENGEMBANGAN MODUL BERNUANSA ISLAMI DALAM PEMBELAJARAN MATEMATIKA PADA MATERI STATISTIKA UNTUK PESERTA DIDIK SMA KELAS XI IPA - Usmadi Usmadi; Iftitahurrahmah Iftitahurrahmah; Ergusni Ergusni (INSPIRAMATIKA, 2022)
ABSTRACT This research aims to produce teaching materials in the form of mathematics learning modules with Islamic nuances. Islamic modules are a teaching material that combines mathematics with religious science. This research is development research (Research Development). The research method is using four D (4-D). This model consists of 4 stages but in this study only 3 stages are defined ( define ), design (design) and development (develop). The type of data used is qualitative data obtained from teacher interviews and observation sheets regarding the practicality of modules. Quantitative data is obtained from the results of module validation, and the practical response questionnaire of learners. The results of this study are Islamic Mathematics Learning Modules in Statistics material. The modules developed were piloted at SMAN 2 Padangpanjang. The results of the trial showed the results that the Islamic mathematics learning module developed was valid with a percentage of 72.3% and practical with a percentage of 87.13%. Practical value is obtained from observations by observers, response questionnaire sheets by students and interview sheets by mathematics teachers. Keywords: Modules, Islamic Concepts, Islamic mathematics learning